63 Quality Improvement Project: Should We be Doing More or Less Ct Head Scans in the Health Care of Older People Department?. (6th February 2020) - Munir, M; Shouter, T; Tay, H S
Abstract: Introduction: Older people are likely to have more CT head scans given their multiple co- morbidities, being on anticoagulants, and increased falls. The aims of this quality improvement project (QIP) were to identify the number of patients who had CT head scan, the reason/indication of it, the number of patients who had new finding/s on it, actions taken on new findings, and whether the management plan was altered because of the CT scan. Methods: Medical notes and CT head scan reports of all patients admitted to the Health Care of Older People department from April to September 2018 were reviewed to evaluate the indications of CT head scans, new findings, and management plans following the findings. Results: 461 (10.7%) out of the 4323 patients discharged from the healthcare of older people department during April to September 2018 had CT head scans during admission. Frequent indications for CT head scans included delirium, falls and head injury. Only 46 (9.9%) patients had new finding/s on the CT head scan, and action was taken on 26 (56.5%) of these patients. The CT head scan changed the management plan of only 17 (3.6%) patients. Please see Table for more details. Conclusions: By using our clinical judgement, following NICE guidelines on head injuries, educating our colleagues on the criteria for requesting a CT head scan, taking collateral histories about patients' cognition and ascertaining the mechanism of fall, we can lessen the financial burden on the NHS and minimise the radiation exposure to our patients.